Analysis of the clinicopathological characteristics, genetic phenotypes, and prognostic of pure mucinous adenocarcinoma. (25th November 2019) - Chen, Zhencong; Li, Ming; Ma, Ke; Shang, Guoguo; Liang, Jiaqi; Yin, Jiacheng; Luo, Jizhuang; Zhan, Cheng; Shi, Yu; Wang, Qun
Abstract: Background: Primary pure mucinous adenocarcinoma of the lung (PMA) is a rare subtype. However, correlations between clinicopathological features and genetic phenotypes with survival have not been described comprehensively. Methods: Pure mucinous adenocarcinoma patient information collected from the Surveillance, Epidemiology, and End Results (SEER) database, the Department of Thoracic Surgery, Zhongshan Hospital, Fudan University (FDZSH), and the Cancer Genome Atlas (TCGA) were extracted, evaluated, and compared with other lung adenocarcinomas (LUAD) patient data. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed to explore the functional importance of underlying molecular changes. Overall survival (OS) was evaluated with the Kaplan‐Meier method. Univariate and multivariate analysis through Cox proportional hazard regression identified risk factors that predicted OS, and the results were used to construct a nomogram to predict OS for PMA patients. Results: Overall, 3622 patients, 41 patients, and 15 patients with PMA were identified from the SEER, FDZSH, and TCGA databases, respectively. There were 345 differentially expressed genes, 30 differentially mutated genes and 72 differentially methylated genes were identified between PMA and other LUAD samples. In the SEER database, PMA had a better prognosis compared to other LUAD. Compared with patients with other LUAD, patients with PMA exhibited unique clinicopathological features, including fewer grade III/IV tumors, less pleural invasion, more early‐stage cancer, and more lower lobe carcinomas. Multivariate analyses showed that age, race, T stage, N stage, surgery, and chemotherapy were independent risk factors. The nomogram had a calibration index of 0.724. Conclusions: Our research identified unique clinicopathological characteristics and genetic phenotypes for PMA and other LUAD. The nomogram accurately predicted OS. Abstract : Clinicopathological characteristics, genetic phenotypes and prognosis factors of primary pure mucinous adenocarcinoma of the lung should be studied in depth. To address this issue, we conducted this large population‐based study. Finally, several clinicopathological features and genetic phenotypes have even been associated with survival in our study. For example, age, race, T stage, N stage, surgery, and chemotherapy were independent risk factors; thyroidtranscription factor‐1 gene and polycomb group ring finger protein 6 gene were relevant to survival.